Online Booking Systems for Managing Queues at The Road Transport Department - E Mohamad; I Anak Jiga; R Rahmat; A Azlan; M.S Abd Rahman; A Saptari (JIE Scientific Journal on Research and Application of Industrial System, 2019)
In Malaysia, the Road Transport Department (RTD) is one of the public sectors facing the issue of having excessive waiting times at their service counter. Various alternatives have been proposed to address this problem, such as implementing an e-government service via the official RTD portal and creating other units so that the demand can be segregated, which also involves the creation of other agencies including myEG and UTC. However, the problem has persisted and has even become one of the most urgent policy issues that plague the RTD. Thus, this study aims to propose an online system that will help manage queue during the service and therefore optimise the waiting time. Several methods were employed to achieve the objectives, including conducting semi-structure interview, observation, and time study at RTD Bukit Katil, Melaka, developing the online system with Adobe Dream Weaver, Oracle SQL Developer software, and Adobe Cold Fusion, and validating and verifying the system using usability studies and questionnaires. The first online system involves an online queue number booking system. With this developed system, clients can use an online system to book their queue number. Furthermore, this system provides clients with the duration of the waiting time so that they can be present at the counter in time before their assigned service. The second proposal involves utilising an online queue booking system. With this system, clients can book their appointment according to the specific time with the RTD staff. This system also makes it possible for the client to come and to be serviced on time. This system aims to optimise the waiting time at the RTD, improve customer satisfaction, and serve as a reference for other government agencies so that their services can be improved